1993
DOI: 10.1055/s-2007-997954
|View full text |Cite
|
Sign up to set email alerts
|

200 freie Jejunumtransplantationen: Lohnt der große operative Aufwand?*

Abstract: From 1983 to 1992, 216 free jejunal transplants were performed after resection of malignant tumours for reconstructing the upper oesophageal tract. In two patients reconstruction was performed secondarily and in four cases within the framework of recurrence treatment. In 25 cases the jejunal transplant was sewn in tubular form to the circular insert of the hypopharynx, whereas in the remaining 188 cases the jejunum transplant was sewn as patch. A jejunum transplant was most frequently employed in the tonsillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Other authors have reported 51% for the 2-year period 16 and 25±40% for 5-year survival. 4,7,19 Our ®ndings are similar to those described by other authors, who have reported failure rates between 3% and 11% (Table 2). 4,9,12,20 In comparison with gastric pull-up (Table 3), the total complication rate associated with the jejunal graft is lower.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Other authors have reported 51% for the 2-year period 16 and 25±40% for 5-year survival. 4,7,19 Our ®ndings are similar to those described by other authors, who have reported failure rates between 3% and 11% (Table 2). 4,9,12,20 In comparison with gastric pull-up (Table 3), the total complication rate associated with the jejunal graft is lower.…”
Section: Resultssupporting
confidence: 91%
“…In our series, the 2‐year survival rate was 59% (13 out of 22 patients) and the 5‐year survival rate was 44% (7 out of 16 patients). Other authors have reported 51% for the 2‐year period 16 and 25–40% for 5‐year survival 4 , 7 , 19 …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the oral cavity the jejunal graft is superior to any other donor tissue because of its thinness and versatility, especially as far as the three-dimensional reconstruction of large postexcisional defects is concerned. 7 It also seems that the mucosal tissue is sufficient for mechanical loading in the oral cavity. In the pharynx, the jejunum conduit best provides the properties of the tissue replaced and represents less donor-site morbidity and fewer complications than transferred ileum, gastric antrum, or colon.…”
Section: Discussionmentioning
confidence: 99%